Transcending Notation: An Exploration of Padhang-Ulihan and Pathet within Javanese Karawitan Music - R. Setyastama (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2023)
This research aims to explore the manifestation of the immanent-transcendental relationship between Javanese individuals and their deity within their performance art songs. The analysis focused on Javanese scale settings known as pathet, as well as padhang-ulihan structures, which represent Javanese sentence styles in composition. These elements were examined to understand how the Javanese express their emotions and convey their thoughts to their deity. The data for this study were collected using ethnographic methods, including participant observation, in-depth interviews, and literature studies. The findings indicate that, as immanent beings, humans require symbols to communicate with their deities in the transcendental realm. Javanese people embody their way of life and perspectives on the universe through the melodies and song structures of Karawitan, a form of Javanese musical art. The analysis of pathet and padhang-ulihan reveals that Javanese individuals shape their worldview by selecting and playing pathet in conjunction with the coordinated construction of the padhang-ulihan model within a Karawitan musical notation.